Nr4a1 suppresses cocaine-induced behavior via epigenetic regulation of homeostatic target genes - Marco D. Carpenter (Nature Portfolio, 2020)
The regulation of gene expression underlies many forms of learning and behaviour in the mammalian brain. Carpenter et al. define a molecular mechanism whereby Nr4a1 activation leads to persistent changes in gene expression, chromatin and behaviour, in the context of cocaine abstinence.